Update on Thumb Basal Joint Arthritis Surgery. Issue 5 (November 2021) - Trost, Jeffrey G.; Gimenez, Alejandro; Staines, Kimberly Goldie; Netscher, David T.
Abstract : Learning Objectives: After studying this article, the participant should be able to: 1. Comprehend anatomy and biomechanics of the normal and arthritic trapeziometacarpal joint. 2. Evaluate best evidence for diagnosis and for operative and nonoperative treatment of thumb osteoarthritis. 3. Understand treatment pitfalls of basilar joint arthritis and complication avoidance. Summary: Articular and ligamentous anatomy of the trapeziometacarpal joint enables complex motions. Disability from arthritis, common at the trapeziometacarpal joint, is debilitating. Furthering the understanding of how trapeziometacarpal arthritis develops can improve treatment. The authors provide current best evidence for diagnosis and treatment of basilar joint arthritis. Pitfalls in treatment are discussed.